2011
DOI: 10.4314/pamj.v9i1.71190
|View full text |Cite
|
Sign up to set email alerts
|

The development of cardiac surgery in West Africa - the case of Ghana

Abstract: West Africa is one of the poorest regions of the world. The sixteen nations listed by the United Nations in this sub-region have some of the lowest gross domestic products in the world. Health care infrastructure is deficient in most of these countries. Cardiac surgery, with its heavy financial outlay is unavailable in many West African countries. These facts notwithstanding, some West African countries have a proud history of open heart surgery not very well known even in African health care circles. Many Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 21 publications
1
81
0
Order By: Relevance
“…Increasing patient volumes in cardiac surgery is essential in boosting confidence of operating teams and refining critical skills that would enhance the development of centers for cardiac surgery and help to improve outcomes 8 . Access to needed cardiac surgery can be increased if locally based private foundations directly contribute to costs of open heart surgery program 7 together with greater direct government funding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing patient volumes in cardiac surgery is essential in boosting confidence of operating teams and refining critical skills that would enhance the development of centers for cardiac surgery and help to improve outcomes 8 . Access to needed cardiac surgery can be increased if locally based private foundations directly contribute to costs of open heart surgery program 7 together with greater direct government funding.…”
Section: Discussionmentioning
confidence: 99%
“…Edwin et al reported mortality rates of 3% among patients with congenital heart disease undergoing open heart surgery, with a reduction in mortality with increase in the volumes of patients operated 8 . The low postoperative morbidity encountered in this study could be attributable to rigorous patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, Nigeria's West African neighbour, the first open heart surgery was done in 1964 using the technique of surface cooling by a team led by professor C. O Easmon, just few years after Gibbon did his famous ASD using CPB [19]. Later, political instability and economic downturn affected this developmental work.…”
Section: Discussionmentioning
confidence: 99%
“…Later, political instability and economic downturn affected this developmental work. With the return of a German trained Ghanaian, Professor Frimpong Boateng, the cardiac surgery became reawakened in 1989 and the establishment a cardiac center in Ghana in 1992, created a watershed in the practice of cardiac surgery in the West African subcontinent [19]. Between 1992 and 1995, Edwin et al 2009 emphasized that about 100-120 cases of cardiac operations were carried out in the center averaging of about 25-30 cases per year and by the year 2008, about 464 operations had been done, with intra-cardiac operations constituting about 25% [20].…”
Section: Discussionmentioning
confidence: 99%
“…6,23 His leadership and long-term vision for health care in Africa have been the primary ingredients for the program's success.…”
Section: Successesmentioning
confidence: 99%